Pengelolaan, Pengawasan Kawasan Pesisir dan Laut di Indonesia - Basri, Hasan (Universitas Malikussaleh, 2020)
This research is a literature study on the management and supervision of coastal and marine areas in Indonesia. The results showed that coastal and marine areas with their natural resources have an important meaning for economic development, because coastal and marine areas are areas with biological and non-biological resources that are very productive. In addition, coastal and marine areas still have a number of critical problems related to ecological, socio-economic and institutional issues. Ecological problems can be observed from the phenomenon of damage to coral reefs, mangrove forests, pollution, overfishing, coastal abrasion and physical degradation of other coastal habitats. It is essentially aimed at empowering the socio-economy of the community, so the community should have contributed to organize themselves in managing coastal and marine resources in this autonomy era. The process of transferring power from government to society must be realized. However, there are a number of things that are still the responsibility of the government, such as matters of fiscal resources policy, development of facilities and infrastructure, preparation of coastal spatial planning, and resource management legal instruments. Even though this is part of the government's authority, it does not mean that the community does not have the contribution and participation in every policy formulation. With the contribution and participation of the community, the formulated policy will touch more on the real issue and not harm the public interest.